Non-communicable diseases in the Western Area District, Sierra Leone, following the Ebola outbreak - Koroma, Ibrahim Baimba (F1000Res, 2019)
Background: Non-communicable diseases (NCDs) are the leading causes of morbidity and mortality in the world. During infectious disease outbreaks, such as the Ebola virus disease outbreak in West Africa from 2014-2015, the health system is often strained, and diagnosis, management and care of NCDs may be compromised. This study assessed numbers and distribution of NCDs in all health facilities in the Western-Area District, Sierra Leone, in the post-Ebola period (June–December 2015) comparing findings with the pre-Ebola (June–December 2013) and Ebola outbreak (June–December 2014) periods. Methods: This was a cross-sectional study using secondary data from routine records of aggregate monthly NCD reports. Data were analysed using Open EPI and comparisons were made between the post-Ebola and pre-Ebola/Ebola periods using the chi-square test. Results: There were 10,011 people reported with NCDs during the three six-month periods, with 6194 (62%) presenting at peripheral health units (PHU). Reported NCDs decreased during Ebola and increased post-Ebola, but did not recover to pre-Ebola levels. Hypertension cases remained fairly constant throughout being mainly managed at PHU. Numbers with diabetes mellitus generally stayed the same except for a significant post-Ebola increase in tertiary hospitals. Small numbers were reported with mental health disorders across all facilities in all time periods. Conclusion: NCD reporting is recovering in the immediate post-Ebola period. Decentralization of NCD care is welcome and is an effective strategy for management as evidenced by hypertension. To be successful, this must be supported by strengthening other elements of the health system such as training of health workers, robust information and referral systems and reliable medicine supply chains.